CORPORATE FINANCIAL MANAGEMENT IN THE DIGITAL ERA: A COMPREHENSIVE LITERATURE REVIEW - Loso Judijanto; Desi Yuniarti (CV. Adiba Aisha Amira, 2024)
The digital era has brought significant changes in various aspects of business, including corporate financial management. The research method used was a literature review. The results showed that digitalisation has fundamentally changed the financial management landscape, with the application of technologies such as artificial intelligence, blockchain, and big data analytics offering increased efficiency and accuracy in financial decision-making. However, this transformation also brings new challenges, particularly in terms of data security, privacy and the need for digital upskilling among finance professionals. The study also revealed a shift in the role of the finance function to become more strategic, with a greater focus on predictive analysis and scenario planning. Implications for the future include the need for a more adaptive approach to financial management, the importance of cross-functional integration within organisations, and continued evolution in financial regulation to accommodate digital innovation.